Causes of growth and stagnation in the world economy - Kaldor, Nicholas (New York, 1996)
In this series of five lectures, Professor Kaldor explores the dynamic forces that govern the growth rate of individual countries and also the growth of the world economy as a closed system. In the first lecture he highlights what he regards as the deficiences of the Walrasian general equilibrium theory for understanding the process of change in dynamic capitalist economies. In the second lecture he proceeds to an analysis of alternative approaches to growth theory from the classics through Marx to Keynes. In the third lecture an innovative and elegant two-sector model is presented of the interaction between the primary producing sector and industrial sector of the world economy which highlights the importance of an equilibrium terms of trade for maximising the growth of output for the world economy as a whole. In the fourth lecture, the role of foreign trade and the balance of payments is used in the explanation of inter country growth performance. Finally in the fifth lecture, Professor Kaldor discusses contemporary economic problems in the world economy. The lectures are followed by an extensive discussion, with contributions from distinguished Italian economists including Amato, Becattini, Pasinetti, Sylos Labini, Lombardini, and Targetti.
Keywords: Growth theory